Mechanochemistry and oleochemistry: a green combination for the production of high-value small chemicals - Len, Christophe; Duhan, Vaishaly; Ouyang, Weiyi; Nguyen, Remi; Lochab, Bimlesh (Frontiers in Chemistry, 2023)
Mechanochemistry and oleochemistry and their combination have been known for centuries. Nevertheless, bioeconomy and circular economy concepts is much more recent and has motivated a regain of interest of dedicated research to improve alternative technologies for the valorization of biomass feedstocks. Accordingly, this review paper aims essentially at outlining recent breakthroughs obtained in the field of mechanochemistry and oleochemicals such as triglycerides, fatty acids, and glycerol derivatives. The review discusses advances obtained in the production of small chemicals derived from oils with a brief overview of vegetable oils, mechanochemistry and the use of mechanochemistry for the synthesis of biodiesel, lipidyl-cyclodextrine, dimeric and labelled fatty acids, calcium diglyceroxide, acylglycerols, benzoxazine and solketal. The paper also briefly overviews advances and limits for an industrial application. This is a provisional file, not the final typeset article and develop chemical processes that are more environmentally friendly, sustainable, and less hazardous. Mechanochemistry contributes to these goals by promoting efficient, solvent-free, and energy-saving reactions. It eliminates or minimizes the use of toxic or harmful reagents and reduces waste generation. Additionally, mechanochemical processes often require lower temperatures, lowering energy consumption and greenhouse gas emissions. The technique also enhances reaction selectivity, leading to fewer byproducts and less need for purification steps. This synergy between mechanochemistry and green chemistry fosters innovation in the development of cleaner, more sustainable chemical processes. It opens the door to more eco-friendly manufacturing, benefiting both the environment and the chemical industry, making it a crucial component of sustainable chemistry practices. Among the promising alternatives to tackle future challenges are renewable resources such as vegetable oil (